Drafting and assessing poetry a guide for teachers - Dymoke, Sue 1962-
Sue Dymoke's practical volume on poetry in the classroom is based on theory but with a practical dimension and combines critical commentaries with illustrations of successful classroom practice to address this under-explored aspect of English teaching
Keywords: English language -- Rhetoric -- Study and teaching; Poetry -- Authorship -- Study and teaching; Creative writing -- Study and teaching